Analysis of Factors Affecting Life Style on Obesity in Global Prima National Plus School Medan in 2018 - Susanti, Prayitna; Lestari Ramadhani Nasution, Sri; Ermi Girsang, Ermi (CV. Inara, 2022)
Obesity is one of the health problems that exist among teenagers, the inability of students to manage your diet be one cause of obesity. Good nutritional status can only be achieved if based on diet on the principle of a balanced menu. The purpose of this study was to determine the effect of lifestyle on obesity in school.The type of research used is a cross-sectional survey with an explanatory research method approach. the number of population according to exclusion criteria is 40 people and the inclusion criteria are 70 people. The data were analyzed using chi square test and linear regression with dummy variables to assess the effect of the dependent variable through independent variables. the results showed that there was a statistically significant dietary pattern of obesity 0.001 (p = 0.005) and the dietary B constant value of 26, 56, 2.21, which means that if a person with a diet is not good as a single risk factor then the body's BMI will increase by 2.21 kg / m2 from the base value of 26.56 kg / m2. And there is a statistically significant relationship between physical activity towards obesity 0.032 (p = 0.05) and B value from the constant physical activity is 26.56, -1.77 means if the respondent has a risk factor in the form of mild physical activity which is also a factor the respondent's single risk of eating will experience an increase in body BMI of 1.77 kg / m2 from the base value of 26.56 kg / m2. while other risk factors such as sleep duration (p = 0.220), snacks (p = 0.1552), socioeconomic status (p = 0.060), school role (p = 0.721), and gadged usage duration (p = 0.274) has a value of p> 0.05, which means that the risk factors did not provide a statistically significant influence on the increase in BMI in the respondents in this study. It is hoped that the school will pay more attention to the nutritional state of the students in the school.